(2x+3)(x+3)
Equation: 9X-3+4X=-2X You are going to want to factor this equation into something that looks like X=35, 35 being a randomly selected number. Step 1) Add 3 to both sides 9X+4X=-2X+3 Step 2) Add 2X to both sides 9X+4X+2X=3 Step 3) Simplify 15X=3 Step4) Divide both sides by 15 X=3/15
Multiply the first equation by 3 to give 9x + 15y = 21
9x - 3(x + 13y) = 9x - 3x - 39y = 6x - 39y = 3(2x - 13y)
2x^3-3x^2-11x+7x+32x^2-9x+16 R -41x+3 l 2x^3-3x^2-11x+7-(2x^3+6x^2)-9x^2-11x+7-(-9x^2-27x)16x+7-(16x+48)-412x^2-9x+16-[41/(x+3)]
2x+3=9x 3=9x-2x 3=7x x=3/7
khjgfsddfghjfghjk
2x+3=9x-2x -2x3=7x/7 /73/7=x
2x + 3 = 9x Subtract 2x from both sides: 3 = 7x Divide both sides by 7: 3/7 = x
X= -2
2x+5=11 2x=6 x=3
2x + 3 = 9x start by bringing the 2x over- minus it from both sides 3 = 7x divide 7 by on sides x= 3/7 x = .4285714285714 repeating.
2x + 3 = 9x start by bringing the 2x over- minus it from both sides 3 = 7x divide 7 by on sides x= 3/7 x = .4285714285714 repeating. :)
2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9
2x + 6 + 9x = 39 11x + 6 = 39 11x = 39 - 6 11x = 33 x = 3
2x+3=9 2x=9-3 2x=6 2x/2=6/2 X=3
6x2 + 9x = 0 3x(2x + 3) = 0 3x = 0 or 2x + 3 = 0 x = 0 or x = -3/2